P4.19 CARDIOVASCULAR RISK FACTORS AND LEFT VENTRICULAR HYPERTROPHY IN CHILDREN WITH CHRONIC KIDNEY DISEASE - Dorota Drozdz*; Przemko Kwinta; Zbigniew Kordon; Katarzyna Zachwieja; Monika Miklaszewska; Krystyna Sztefko; Andrzej Rudzinski; Jacek Antoni Pietrzyk (Artery Research, 2015)
Cardiovascular diseases are substantial causes of mortality among patients with chronic kidney disease (CKD). The aim of the study was an assessment of the impact of cardiovascular risk factors on left ventricular hypertrophy (LVH) in children with CKD. Material and methods: The study was conducted in a group of 71 children with mean age 11 years and CKD stage 1 to 5. Serum cystatin C, albumin levels, and lipids profile were measured. Ambulatory blood pressure measurements and echocardiography were performed. Results: LVH was detected in 34 out of 71 children. In children with LVH, significantly higher values of BP were observed in 24-hour measurements: systolic (119 vs. 109 mm Hg; p=0.002), diastolic BP (73 vs. 65 mm Hg; p=0.009) and MAP (89 vs. 81 mm Hg, p=0.004). These significantly higher BP values were observed within day and night. Increased cholesterol level was found in 25, LDL in 12, TGL in 28, and a decreased HDL in 20 children. In children with LVH higher BMI (18.6 vs. 16.7 kg/m2;p=0.039) and lower albumin (41.5 vs. 45.4 g/l; p=0.013), HDL (1.14 vs. 1.5 mmol/l; p=0.001) and Ca levels (2.36 vs. 2.47 mmol/l; p=0.03) were found. Obesity and low HDL level were independent LVH risk factors. The results indicate a 3-fold increase in the risk of LVH in children with hypertension (OR 3.18, p=0.045), rising up when 2-3 risk factors were present (OR 6, p=0.015). Conclusions: Hypertension, a decreased HDL cholesterol level and overhydration have significant impact on the development of LVH in CKD children.